The macroeconomic determinants of tax revenue : the case of Malaysia / Nurul Izzaty Anuar - Anuar, Nurul Izzaty (Faculty of Business and Management, 2019)
Almost every year Malaysia is facing budget deficit which means more money being spent than is coming in via taxes and other income. Last year in 2017, a government budget deficit had been recorded by Malaysia which equal to 3 percent of the country's gross domestic product (GDP). Government budget in Malaysia averaged -2.97 percent of GDP from 1988 until 2017, record low of -6.70 percent of GDP in 2009 and reaching an all-time high of 2.40 percent of GDP in 1997. Only throughout year 1993-1997 Malaysia faced budget surplus while the rest was the budget deficit. Thus, this study aims to identify the major factors that influence the tax revenue in Malaysia. Therefore, the study carried out to analyze the significant relationship between the dependent variable and the independent variables either affected positively or negatively. This current study employs a regression model in examining the macroeconomic determinants of tax revenue in Malaysia. This study is using annually time series data over the period from 1980 to 2015. The study involved four selected variables which are Inflation Rate (INF), Trade Openness (OPN), Exchange Rate (EXC) and Value-added of Agriculture Sector (AGR). The findings resulted that EXC is associated as the major factors that influence the tax revenue in Malaysia. In fact, inflation rate, trade openness and exchange rate were found to be significantly affect the tax revenue. Consequently, inflation rate and exchange rate were positively related to the tax revenue while trade openness was negatively related. However, the value-added of agriculture sector was insignificant factor that can affect the tax revenue where it have a negative relationship toward the tax revenue.